Monitoring Perubahan Lahan Terbangun Menggunakan Algoritma NDBI di Kecamatan Kabila Kabupaten Bone Bolango - Djafar, Egitya Saputra; Lihawa, Fitryane; Maryati, Sri (-, 2025)
This study analyzes changes in built-up areas in Kabila District, Bone Bolango Regency, using the Normalized Difference Built-Up Index (NDBI) derived from Landsat 8 imagery from 2017, 2020, and 2023. Multitemporal satellite data were processed using ArcGIS to calculate NDBI values and map the spatial distribution of built-up land. NDBI values increased from 0.143 in 2017 to 0.132 in 2020, and continued to rise in 2023. Built-up areas expanded from 512.35 hectares (40.96%) in 2017 to 546.18 hectares (43.62%) in 2020, and reached 570.35 hectares (45.6%) in 2023. The expansion mainly occurred in the central and southern areas, indicating urban growth and land conversion from agricultural to residential use. This shift potentially contributes to higher surface temperatures and reduced thermal comfort. The study highlights the importance of spatial data in monitoring urban development and provides essential input for sustainable and adaptive spatial planning in response to increasing development pressures.